A facile method for cellular N-glycomic profiling by matrix-assisted laser desorption/ionization mass spectrometry. Issue 57 (20th July 2017) - Gao, Wenjie; Jiang, Yanhua; Zhang, Zhihui; Zhang, Yifang; Liu, Yanyan; Zhou, Yanhong; Liu, Xin
Abstract : Rapid and highly sensitive analysis of cellular N -glycans with co-derivatization strategy using matrix-assisted laser/desorption mass spectrometry. Abstract : Conventional protocols for cellular N -glycan profiling often need several time-consuming and labor-intensive steps, and a large amount of material (5–20 × 10 6 cells) is required. In this study, an optimized co-derivatization method was applied for convenient, rapid and highly-sensitive analysis of cellular N -glycan. Taking human cervical carcinoma cells (HeLa) as a model, the required amount for comprehensive cellular N -glycans analysis was reduced down to an original cell number of 10 5 and the total analysis time was decreased from several days to several hours. Good reproducibility of the method was also obtained with the CV averaging to less than 13.1%. In addition, compared to permethylation derivatization, more than 5-fold sensitivity improvement was achieved and more concise and clear mass spectra were obtained with the new developed method. As a preliminary study, this method was also successfully applied to reveal the difference in cellular N -glycan profiling of two heterogeneous live cell lines, human normal liver cells (L-02) and human hepatocyte carcinoma cells (HepG2), showing great potential for high-throughput analysis of N -glycans from limited cell samples, such as primary cell lines, cells obtained from cell sorting and small size cancer specimens.